Properties of BK-type Ca++-dependent K+ channel currents in medial prefrontal cortex (PFC) pyramidal neurons in rats of different ages - Książek, Aneta; Ładno, Wioletta; Szulczyk, Bartłomiej P.; Grzelka, Katarzyna; Szulczyk, Paweł J. (Frontiers in Cellular Neuroscience, 2013)
The medial prefrontal cortex (PFC) is involved in cognitive functions, which undergo profound changes during adolescence. This alteration of the PFC function derives from neuron activity, which, in turn, may depend on age-dependent properties and the expression of neuronal ion channels. BK-type channels are involved in controlling both the Ca++ ion concentration in the cell interior and cell excitability. The purpose of this study was to test the properties of BK currents in the medial PFC pyramidal neurons of young (18–22-day-old), adolescent (38–42-day-old) and adult (58–62-day-old) rats. Whole-cell currents evoked by depolarizing voltage steps were recorded from dispersed medial PFC pyramidal neurons. A selective BK channel blocker – paxilline (10 µM) – irreversibly decreased the non-inactivating K+ current in neurons that were isolated from the young and adult rats. This current was not significantly affected by paxilline in the neurons obtained from adolescent rats. The properties of single-channel K+ currents were recorded from the soma of dispersed medial PFC pyramidal neurons in the cell-attached configuration. Of the K+ channel currents that were recorded, 90% were BK and leak channel currents. The BK-type channel currents were dependent on the Ca++ concentration and the voltage and were inhibited by paxilline. The biophysical properties of the BK channel currents did not differ among the pyramidal neurons isolated from young, adolescent and adult rats. Among all of the recorded K+ channel currents, 38.9%, 12.7% and 21.1% were BK-type channel currents in the neurons isolated from the young, adolescent and adult rats, respectively. Furthermore, application of paxilline effectively prolonged the half-width of the action potential in pyramidal neurons in slices isolated from young and adult rats but not in neurons isolated from adolescent rats. We conclude that the availability of BK channel currents decreases in medial PFC pyramidal neurons of adolescent rat